2017
DOI: 10.1039/c7ra01798g
|View full text |Cite
|
Sign up to set email alerts
|

Co9S8@N,P-doped porous carbon electrocatalyst using biomass-derived carbon nanodots as a precursor for overall water splitting in alkaline media

Abstract: In this study, we first synthesized Co 9 S 8 @N-doped porous carbon (Co 9 S 8 @NC) using shrimp-shell derived carbon nanodots as a carbon/nitrogen source in the presence of CoSO 4 by a one-step molten-salt calcination method. This was followed by low-temperature phosphorization in the presence of NaH 2 PO 2 , whereby Co 9 S 8 @N,P-doped porous carbon (Co 9 S 8 @NPC) was finally obtained using the Co 9 S 8 @NC as a precursor. The results demonstrated that the molten-salt calcination approach can effectively cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 52 publications
(40 reference statements)
2
33
0
Order By: Relevance
“…In comparison to bulk Co 9 S 8 , nanostructured Co 9 S 8 and its composites could afford more active sites and faster transfer rate of ions/electrons during the electrocatalytic reaction, and thus usually exhibiting enhanced HER and OER activities. [20][21][22][23][24] Currently, several Co 9 S 8 nanostructures (e.g., nanoparticles [25] and nanospheres [26] ) and their composites with carbons (Co 9 S 8 /reduced graphene oxides (RGO), [22] Co 9 S 8 /(N, S, P)-doped carbons, [27] Co 9 S 8 /Fe 3 O 4 / RGO, [23] and Co 9 S 8 /MoS 2 /Carbon fibres [25] ) have been reported. For example, Co 9 S 8 /N,P-carbon powder nanocomposites prepared by molten-salt calcination method at 900 °C exhibited an HER overpotential of 261 mV at 10 mA cm −2 in alkaline medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to bulk Co 9 S 8 , nanostructured Co 9 S 8 and its composites could afford more active sites and faster transfer rate of ions/electrons during the electrocatalytic reaction, and thus usually exhibiting enhanced HER and OER activities. [20][21][22][23][24] Currently, several Co 9 S 8 nanostructures (e.g., nanoparticles [25] and nanospheres [26] ) and their composites with carbons (Co 9 S 8 /reduced graphene oxides (RGO), [22] Co 9 S 8 /(N, S, P)-doped carbons, [27] Co 9 S 8 /Fe 3 O 4 / RGO, [23] and Co 9 S 8 /MoS 2 /Carbon fibres [25] ) have been reported. For example, Co 9 S 8 /N,P-carbon powder nanocomposites prepared by molten-salt calcination method at 900 °C exhibited an HER overpotential of 261 mV at 10 mA cm −2 in alkaline medium.…”
mentioning
confidence: 99%
“…For example, Co 9 S 8 /N,P-carbon powder nanocomposites prepared by molten-salt calcination method at 900 °C exhibited an HER overpotential of 261 mV at 10 mA cm −2 in alkaline medium. [20] N-Co 9 S 8 /graphene nanocomposites was achieved Designing ever more efficient and cost-effective bifunctional electrocatalysts for oxygen/hydrogen evolution reactions (OER/HER) is greatly vital and challenging. Here, a new type of binder-free hollow TiO 2 @Co 9 S 8 core-branch arrays is developed as highly active OER and HER electrocatalysts for stable overall water splitting.…”
mentioning
confidence: 99%
“…The high‐resolution C 1s spectrum (Figure d) can be deconvoluted into four peaks at 284.6, 285.2, 286.1, and 290.0 eV, which correspond to CC/CC, CN, CO, and CO, respectively . The high resolution N 1s spectrum (Figure e) can be deconvoluted into four peaks, which are correlated to various electronic states of nitrogen functional groups, such as pyridinic N (398.7 eV), pyrrolic N (399.9 eV), graphitic N (401.2 eV), and quaternary N (402.4 eV), indicating successful doping of nitrogen into the carbon matrix . This is due to the fact that the nitrogen doping can improve the electrical conductivity of the carbon matrix, which results in improved electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…Of these candidates, cobalt sulfide (Co 9 S 8 ) has been the subject of intense research because of its high catalytic activity and superior electrochemical stability for OER [18,19] . Though cobalt sulfide is endowed with these fascinating virtues, the OER performance of the bulk Co 9 S 8 is still unsatisfactory due to poor electronic conductivity and little exposed active sites [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, a variety of Co 9 S 8 electrodes have been reported by developing Co 9 S 8 nanostructures or compositing with conductive matrixes. For instance, Co 9 S 8 @N/P-doped carbon composite electrocatalysts prepared by Liu et al [18] exhibited a low overpotential of 400 mV at 10 mA cm −2 by a one-step molten-salt calcination method. Cao et al [23] reported cobalt sulfide/porous N-doped carbon with a low Tafel slope of 65 mV dec −1 by a high-temperature calcination method.…”
Section: Introductionmentioning
confidence: 99%